Le droit à la vie privée des personnes homosexuelles - Goreham, Richard (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
This paper examines the idea of personal privacy and how the law has responded to expectations that it be adequately protected. The legal protection of personal privacy is evaluated in light of the concerns of homosexual persons that information about their sexual orientation remain confidential. Although individual privacy is a notion that can be used to argue for a sphere of individual freedom, in the sense that adult individuals should be free of government restriction on how they express themselves sexually in private, this paper focuses on privacy insofar as it relates to the undesired disclosure of information about a person's private life. This is privacy as secrecy, a concept which is concerned with the degree to which we are prepared to allow people to live their lives free from the intrusive prying of others. Whether the idea of breach of privacy as giving rise to civil responsibility has evolved under tort law is reviewed in the common law of both Canada and the United States. The inadequacy of the common law in protecting a general right to privacy has led to the adoption of a number of provincial statutes which create an invasion of privacy tort, and the importance of these in potentially protecting the privacy of homosexual persons is examined. The recognition of a general right to privacy under the Quebec Civil Code and its reinforcement by provisions in the Quebec Charter of Rights and Freedoms completes the analysis of civil remedies for breach of privacy in Canada. For comparative purposes, the development of the « private facts tort » in the American legal system is explored and commented. Informational privacy as it relates to the collection, storage and use of personal information by governments constitutes the focus of part 3 of this paper. It assesses the dangers inherent in the use and storage of personal information by governments in both Canada and the U.S.A. The recognition of the potential for abuse has resulted in the adoption of Privacy Acts in both countries at the federal level and, with respect to Canada, in the province of Quebec. Such legislation seeks to answer the twin preoccupations of when government institutions are justified in collecting and using personal information and when they are justified in disclosing it. These questions are of considerable importance to homosexual persons and this is emphasized in the analysis. Views on the relationship between privacy and social tolerance are offered in the conclusion to the paper.